EARLY TRADE RELATIONS AND THEIR INFLUENCE ON TERMINOLOGY (In the example of economic and pedagogical terms) (TAMADDUN NURI JURNALI, 2024)
This article refers to the history of the development of trade relations in world history, their changing characteristics and the development of terminology related to various fields as a result of international economic relations. In addition, the economic development of countries from ancient civilizations to the present day is covered, and the historical place of trade and commerce, the paths of their development and their connection with the most important centers of world history, the emergence of economic and pedagogical terms are also considered.